ENVIRONMENTAL EDUCATION AND AWAKENING TO CITIZENSHIP - Rorato, Gelsa Guarienti; Canto-Dorow, Thaís Scotti do; Rorato, Daniele Guarienti; Rosito, Jumaida Maria (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The work has as objective to encourage the participation of students in environmental education activities, arousing interest in native species and their use for restoration of riparian areas of streams and springs in the municipality of São João do Polêsine, RS, Brazil. The research was conducted with students from the 4th and 5th year of Municipal Elementary School La Salle, meetings that covered topics such as the study of native trees, concepts of forest diversity , the environment and conservation areas being conducted, as well as planting native forest species, ecological trail , a walk on the banks of River Soturno, among other activities. there was a big behavioral change in relation to the preservation of the environment in the form of commitment to actions and preservationist attitudes and the desire to forward community concepts and knowledge acquired. Also noting students motivation while performing this job, evidenced by the interest and participation in activities and understanding of concepts worked. Thus, it is perceived that through environmental education can raise awareness about the need of preserving forest diversity through knowledge of native species forming forests existing in the locality, as well as its possible use in the recovery of riparian forests.